(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to describe the clinical and CBCT outcomes of secondary gingivoperiosteoplasty (GPP) for the treatment of unilateral alveolar clefts. Subject and method: Descriptive and prospective study collected data from 28 patients with unilateral alveolar clefts who were clinically monitored before and after the surgery 1 day, 1 month, 6 months and CBCT scans before and after the surgery 6 months. Results: The mean age was 5.7 ± 0.9 years, of which 18 (64.3%) patients were male, 20 (71.4%) patients had left-sided alveolar cleft, 18 (64.3%) patients had alveolar cleft involving the complete cleft palate and 16 (57.1%) patients had a tooth in the cleft. The median time of surgery was 41.5 minutes and the interquartile range was 37 minutes - 53 minutes. After 6 months of the surgery, 100% of patients scored 5 or higher corresponding to the categories of fair, good and very good in terms of clinical aspects, with a 225.9 ± 36.0 mm3 reduction in alveolar cleft volume and 32.1% of patients had a bone bridge across the cleft. Conclusion: GPP for the treatment of unilateral alveolar cleft patients aged 5-7 years old initially showed good results clinically and on CBCT.